(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
We describe and compare a Eurgnathohippus juvenile skull, RMNH67/5665 from site BKII, Olduvai Gorge, ca. 1.2 Ma. Study of the facial morphology and cheek tooth metrical data including length versus width and protocone length versus width of the dP2, 3 and 4 support the conclusion that this juvenile skull is the species Eurygnathohippus cornelianus, and that in turn Eu. cornelianus is a member of the “Sivalhippus” Complex, which includes the following superspecific clades: Sivalhippus, Eurygnathohippus, Plesiohipparion and Proboscidipparion. Recent studies suggest that Eurygnathohippus has a particularly close phylogenetic relationship with Plesiohipparion.